The Rise and Fall of Modern Medicine by James Le Fanu - Bauer, Henry (Journal of Scientific Exploration, 2017)
This is a phenomenally instructive book, a levelheaded analysis, and recommended without reservation. Le Fanu is an MD in general practice in London and a regular columnist for the Telegraph. (The book is written with British spelling, and a few remarks are specific to UK’s National Health Service, but everything is nevertheless relevant internationally, globally.) The instructive first part of the book describes “twelve definitive moments” in the development of modern — i.e. contemporary — medicine: 1941, penicillin; 1949, cortisone; 1950, streptomycin, also smoking and Sir Austin Bradford Hill (epidemiology); 1952, chlorpromazine and revolution in psychiatry; 1952, polio epidemic in Copenhagen and birth of intensive care; 1955, open-heart surgery (the last frontier); 1961, new hips for old; 1963, transplanting kidneys; 1964, triumph of prevention (of strokes); 1971, curing childhood cancer; 1978, the first test-tube baby; 1984, Heliobacter, cause of peptic ulcer. Those episodes are described at length, followed by an analysis of this “Rise” of medicine. Those defining events came from serendipitous discovery of drugs, the development of clinical science, for example Bradford Hill’s statistical epidemiology, and staggering technological innovation: heart-lung machines and laparoscopic surgery. But credit for all this goes not only to the brilliant and persistent pioneering physicians and researchers, Le Fanu credits also “the mysteries of biology”: the unanticipated, unforeseeable fact that antibiotics can be effective against a range of bacterial pathogens, and the equally astonishing fact that cortisone is capable of treating or ameliorating a staggering range and variety of conditions.